Progress in industrial application of γ-butyrolactone - LIANG Bin (Academic Journals Center of Shanghai Normal University, 2021)
γ-butyrolactone (GBL) is an important chemical industrial raw material, which is widely used in industrial raw materials, pharmaceutical intermediates, and new energy materials. These applications provide the possibility for its industrial production. Herein, we summarized the application and development of GBL in industrial raw materials and pharmaceutical intermediates, and discussed its existing problems and possible development direction.